On the Development of a Cutaneous Flavonoid Delivery System: Advances and Limitations - Raquel Costa; Sofia A. Costa Lima; Paula Gameiro; Salette Reis (MDPI AG, 2021)
Flavonoids are one of the vital classes of natural polyphenolic compounds abundantly found in plants. Due to their wide range of therapeutic properties, which include antioxidant, anti-inflammatory, photoprotective, and depigmentation effects, flavonoids have been demonstrated to be promising agents in the treatment of several skin disorders. However, their lipophilic nature and poor water solubility invariably lead to limited oral bioavailability. In addition, they are rapidly degraded and metabolized in the human body, hindering their potential contribution to the prevention and treatment of many disorders. Thus, to overcome these challenges, several cutaneous delivery systems have been extensively studied. Topical drug delivery besides offering an alternative administration route also ensures a sustained release of the active compound at the desired site of action. Incorporation into lipid or polymer-based nanoparticles appears to be a highly effective approach for cutaneous delivery of flavonoids with good encapsulation potential and reduced toxicity. This review focuses on currently available formulations used to administer either topically or systemically different classes of flavonoids in the skin, highlighting their potential application as therapeutic and preventive agents.